Aberrant Brain Signal Variability and COMT Genotype in Chronic TMD Patients. (July 2021) - Lim, M.; Nascimento, T.D.; Kim, D.J.; Ellingrod, V.L.; DaSilva, A.F.
The analysis of brain signal variability is a promising approach to understand pathological brain function related to chronic pain. This study investigates whether blood-oxygen-level–dependent signal variability (BOLDSV ) in specific frequency bands is altered in temporomandibular disorder (TMD) and correlated to its clinical features. Twelve patients with chronic myofascial TMD and 24 healthy controls (HCs) underwent resting-state functional magnetic resonance imaging. The BOLDSV was measured as the standard deviation of the BOLD time series at each voxel and compared between groups. We also examined the potential relationship between the BOLDSV and the catechol- O -methyltransferase ( COMT ) Val 158 Met polymorphism. We assessed sensory-discriminative pain in the craniofacial region, pain sensitivity to sustained masseteric pain challenge, and TMD pain frequency for clinical correlation. Patients displayed reduced BOLDSV in the dorsolateral prefrontal cortex (dlPFC) as compared with HC in all frequency bands. In the slow-3 band, patients also showed reduced BOLDSV in the medial dorsal thalamus, primary motor cortex (M1), and primary somatosensory cortex (S1) and heightened BOLDSV in the temporal pole. Notably, we found a significant correlation between lower BOLDSV (slow-3) in the orofacial M1/S1 regions and higher clinical pain (intensity/area) and higher sensitivity of the masseter muscle pain. Moreover, lower BOLDSV (slow-3) in the dlPFC and ventrolateral PFC was associated with a higher TMD pain frequency. Participants who had the COMT 158 Met substitution exhibited lower BOLDSV in the dlPFC and higher BOLDSV in the temporal pole as compared with participants without the COMT 158 Met substitution. An increasing number of Met alleles was associated with lower dlPFC and greater temporal pole BOLDSV in both HC and TMD groups. Together, we demonstrated that chronic TMD patients exhibit aberrant BOLDSV in the top-down pain modulatory and sensorimotor circuits associated with their pain frequency and severity. COMT Val 158 Met polymorphism might affect clinical symptoms in association with regional brain signal variability, specifically involved in cognitive and emotional regulation of pain.